Kepastian Hukum Sertipikat Hak Milik Berdasarkan Peralihan Hak Jual Beli Terkait Gugatan Ahli Waris - Shafira Alwi; Felicitas Sri Marniati; Mardi Candra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
A certificate is strong evidence of rights. Indonesia adopts a negative publication system with a positive tendency, meaning that a certificate is not absolute proof of land ownership. This means that other parties can still file a lawsuit against the certificate holder if they feel they have rights to the land. Certificates of Ownership obtained through a sale and purchase are related to Article 3 of Government Regulation Number 24 of 1997 concerning Land Registration, which states that to provide legal certainty to holders of rights to land, apartment units, and other registered rights so that they can easily prove themselves as the holders of the rights in question. However, in the context of inheritance lawsuits, the certificate's validity can be re-examined if it is proven to have been obtained through an illegal sale and purchase process, then it can be revoked by the court. The formulation of the problem is: How is the transfer of rights to a Certificate of Ownership based on a sale and purchase related to an heir's lawsuit and How is the legal certainty of a Certificate of Ownership based on the transfer of rights to a sale and purchase related to an heir's lawsuit. In this study, the researcher uses the Land Registration Theory according to Boedi Harsono and the Legal Certainty Theory according to Otto Jan Michael. The research method used in this study is a type of normative legal research, namely legal research with literature studies based on primary, secondary and tertiary legal sources. The research approaches used are the Legislation Approach, Conceptual Approach, Analytical Approach and Case Approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. For the legal material analysis technique, it is carried out with grammatical interpretation, Systematic interpretation, Analogy Construction and legal refinement construction. The research concludes that the transfer of rights based on a sale and purchase made before a PPAT is an official process of transferring land ownership from the seller to the buyer. This deed is legal evidence of the transfer of rights and is required for registration of the transfer of rights at the land office. To ensure legal certainty regarding certificate transfers, regulators should establish an integrated electronic system for stakeholders, including Land Deed Officials (PPAT) and the National Land Agency (BPN). This aligns with the government's e-certificate program. This integrated system improves coordination and information up-to-dateness, including status updates upon court decisions. This rapid and transparent integration provides legal certainty.